Sales Performance Classification of Promotional Products Using Data Mining - Rafli Satria Iswandaru; Aries Dwi Indriyanti (Universitas Negeri Surabaya, 2026)
The objective of this research is to establish a classification model to determine high sales performance promotional products using past sales records. The issue at stake is that it is very hard for business actors to forecast the appearance of high sales promotional products, taking into account different factors, such as product type, price per unit, quantity requested, and sales period. This study, based on a quantitative and experiential manner, makes use of the C4. 5 decision tree algorithms on real transaction data of HERA Promotion during 2024. The data falls into one of two types: